2002
DOI: 10.4049/jimmunol.169.10.5796
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Metastatic Disease in STAT6-Deficient Mice Requires Hemopoietic and Nonhemopoietic Cells and Is IFN-γ Dependent

Abstract: Mice deficient for the STAT6 gene (STAT6−/− mice) have enhanced immunosurveillance against primary and metastatic tumors. Because STAT6 is a downstream effector of the IL-4R, and IL-13 binds to the type 2 IL-4R, IL-13 has been proposed as an inhibitor that blocks differentiation of tumor-specific CD8+ T cells. Immunity in STAT6−/− mice is unusually effective in that 45–80% of STAT6−/− mice with established, spontaneous metastatic 4T1 mammary carcinoma, whose primary tumors are surgically excised, survive indef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 25 publications
7
79
1
Order By: Relevance
“…Note added in proof: Recent work published after this article was submitted has provided additional clarity to the 4T1 tumor model in STAT6 Ϫ/Ϫ mice. The important role of the type 1 cytokine, IFN-␥, was demonstrated by the inability of STAT6 Ϫ/Ϫ IFN-␥ Ϫ/Ϫ mice to survive long term against a 4T1 tumor challenge (41). This was in contrast to STAT6 Ϫ/Ϫ mice, where Ͼ80% of the mice survived for longer than 150 days.…”
Section: Discussionmentioning
confidence: 47%
“…Note added in proof: Recent work published after this article was submitted has provided additional clarity to the 4T1 tumor model in STAT6 Ϫ/Ϫ mice. The important role of the type 1 cytokine, IFN-␥, was demonstrated by the inability of STAT6 Ϫ/Ϫ IFN-␥ Ϫ/Ϫ mice to survive long term against a 4T1 tumor challenge (41). This was in contrast to STAT6 Ϫ/Ϫ mice, where Ͼ80% of the mice survived for longer than 150 days.…”
Section: Discussionmentioning
confidence: 47%
“…It has been shown that the IL-13 and STAT6 pathway play an important role in tumor immunity. 53,54 In addition, IL-13 and CD1d-restricted NKT cells induced production of TGF-β by CD11b + Gr-1 + cells. 55,56 In conclusion, we demonstrate that 35% of TβRI COKO mice developed SCCs 6 months after birth.…”
Section: Discussionmentioning
confidence: 99%
“…This cell turned out to be a CD11b ϩ Gr-1 ϩ myeloid cell that was induced to make TGF-␤, and the TGF-␤ was sufficient to inhibit the CD8 ϩ T cell response, suggesting that this was the effector molecule mediating the suppression (95). Besides this predominant suppressive mechanism involving IL-13 and TGF-␤, NKT cells must be able to suppress by additional mechanisms as observed in the 4T1 mammary carcinoma in which CD1d KO mice and STAT6 KO mice were protected but IL-13 KO mice or mice treated with an IL-13 antagonist were not (99), and as observed in an orthotopic osteosarcoma model in which CD1d KO mice were protected but blockade of IL-13 or TGF-␤ had no effect (100). Studies in other tumor models supported a role for NKT cells in the suppression of tumor immunity, for example in the protection by IL-12 and IL-18 against the liver metastases of a mouse renal cell carcinoma (101).…”
Section: Regulatory Role Of Type I Nkt Cells In Autoimmunity Andmentioning
confidence: 99%